Exergy Analysis of 1 x 135 MW Jeneponto Steam Power Plant - Hamzah, Nur; Yunus, A.M Shiddiq; Al Fadiyah, Waqva Enno (Politeknik Negeri Ujung Pandang, 2020)
Exergy analysis is application of the second law thermodynamics which provides information about large exergy, exergy efficiency, destruction, and destruction efficiency in each component of PLTU so can be reference for improvement and optimization in an effort to reduce losses and increase efficiency. The exergy value obtained from calculating mass flowrate, enthalpy, ambient temperature, and entropy. The destruction value is obtained from difference between input exergy value and exergy output. The destruction exergy value from comparison between output exergy value to input exergy value, and destruction efficiency value from comparison of destruction value to total destruction value of PLTU components. The results showed that the largest exergy occurred in boilers, namely 778.225 MW in 2018, 788.824 MW in 2019, and 796.824 MW in 2020, lowest exergy value in CP was 0.160 MW in 2018, 0.176 MW in 2019, and 0.160 MW in 2020. The largest destruction occurred in boilers, namely 163.970 MW with destruction efficiency 79.242% in 2018, 179.450 MW with destruction efficiency 82.111% in 2019, and 199.637 MW with destruction efficiency 83.448% in 2020, lowest exergy destruction value at CP, namely 0.056 MW with destruction efficiency 0.027% in 2018, 0.059 MW with destruction efficiency 0.027% in 2019, and 0.056 MW with destruction efficiency 0.023% in 2020. The exergy efficiency occurred in HPH 2, amounting to 94.750% in 2018, 95.187 % in 2019, and 94.728% in 2020, while lowest of exergy efficiency was in LPH 1, namely 43.637 MW in 2018, 33.512 MW in 2019, and 38.764 MW in 2020.